‘Flexing’ and its Implications for Religious and Social Life Among Indonesian Muslim Millennials - Rachman, Abdul; Sangare, Bilaly; Suardi, Didi; Jamaludin, Nur; Azwar, Martavevi; Simatupang, Aisyah Defy R.; Karim, Salman Izudin; Aprianto, Muhammad Rafli; Rizky, Teguh Muhammad (Universitas Muhammadiyah Magelang, 2024)
This study investigates the implications of the ‘flexing’ phenomenon, characterized by the ostentatious display of wealth and material possessions on social media, on the religious and social life of Indonesian Muslim millennials. Employing a qualitative research methodology, the study analyzes data collected through social media observation and interviews with millennial Muslims. Findings reveal that ‘flexing’ can have detrimental effects on religious life, including fostering excessive materialism, eroding integrity and honesty, and hindering the fulfillment of Islamic obligations such as Zakat and charitable giving. Furthermore, the study demonstrates that